Pengaruh Strategi Pengembangan Karir Dan Employer Branding Dalam Meningkatkan Kinerja Pegawai Di SMKN 1 Solok Selatan Melalui Loyalitas Sebagai Variabel Intervening - Ferdion Marantika (CV. ITTC INDONESIA, 2026)
This study aims to determine and analyze the Effect of Career Development Strategy and Employer Branding on Employee Performance at SMK N 1 Solok Selatan through Loyalty as an Intervening Variable. The research method used by the author in this study is quantitative research. This study employs a Structural Equation Modeling (SEM) model with SmartPLS 4.1.1.8 as the analysis tool. The population and sample of this study consist of 71 employees of SMK N 1 Solok Selatan. The results of the study found that there is a significant effect of Career Development Strategy on Employee Loyalty. There is a significant effect of Employer Branding on Employee Loyalty. There is a significant effect of Career Development Strategy on Employee Performance. There is a significant effect of Employer Branding on Employee Performance. There is a significant effect of Employee Loyalty on Employee Performance. Employee Loyalty is able to mediate the effect of Career Development Strategy on Employee Performance. Employee Loyalty is able to mediate the effect of Employer Branding on Employee Performance.